2021
DOI: 10.1108/arj-04-2021-0121
|View full text |Cite
|
Sign up to set email alerts
|

From unrequited love to sleeping with the enemy: COVID-19 and the future relationship between UK universities and professional accounting bodies

Abstract: Purpose This paper aims to examine the effects of coronavirus disease 2019 (COVID-19) on the relationship between UK universities and professional accounting bodies (PABs) in the context of the accreditation system and how well prepared this relationship was to observe and respond to the pandemic. Design/methodology/approach The research draws on 10 semi-structured interviews and correspondence, with six English universities in the context of their relationship with three PABs to build an extended analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Repeated use of particular words indicated that these ideas were valuable and important in respondents' lived experiences. Here, we borrowed an approach used by (Riaz et al 2022 andAl Mahameed et al 2021), where unique words repeatedly used were identified, and the number of times each was usedand the number of respondents who used them. This information enabled us to formulate a theme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated use of particular words indicated that these ideas were valuable and important in respondents' lived experiences. Here, we borrowed an approach used by (Riaz et al 2022 andAl Mahameed et al 2021), where unique words repeatedly used were identified, and the number of times each was usedand the number of respondents who used them. This information enabled us to formulate a theme.…”
Section: Discussionmentioning
confidence: 99%
“…In the current paper and interviewing the management, we spoke with academics. It is widely accepted that businesses and powerful institutions (such as universities) are critical in the transition toward a sustainable economy, given their influence and control in our societies (Gray and Milne, 2004;Schneider, 2015;Al Mahameed et al, 2022). Exploring the implementation of sustainability practices in an increasingly competitive higher education sector within a local setting will shed light on the roles of a range of actors and how their involvement influences existing practices, decisions, and direction of the institute.…”
Section: The Concept Of Sustainabilitymentioning
confidence: 99%
“…Whether accounting education within UKHE needs to be aligned to that determined by the professional bodies is still open for debate. Accounting departments within universities still view alignment to professional bodies and exams as a key priority for their courses (Al Mahameed et al , 2022). Efforts within professional examination syllabi to incorporate more holistic skill sets should be noted; however, the desire to standardise accounting education (McPeak et al , 2012) prevents a barrier to this, as standardisation potentially leaves little consideration for cultural and human factors specific to a more pluralistic approach (Helliar, 2013).…”
Section: The Paradox Of Accounting Education: Educate To Be Accountan...mentioning
confidence: 99%
“…Nonetheless, a university degree is perceived as desirable rather than essential when it comes to the job market. Although many accountants hold a university degree, it is often desirable rather than essential, and often, the degree can be in any subject (Al Mahameed et al , 2022).…”
Section: The Paradox Of Accounting Education: Educate To Be Accountan...mentioning
confidence: 99%
See 1 more Smart Citation